Isi Kandungan Dakwah dalam Media Akun Instagram Inspiratif Asmam - Samalateh, Ausen (Komunika: Journal of Communication Science and Islamic Dakwah, 2020)
This research is a research of the contents of the da'wah content in the inspirational, asmam instagram account media. the purpose of this research is how the contents of the da'wah content in the inspirational instagram account media and how to deliver the da'wah in the inspirational video asmam.The research method used is qualitative while the approach used to understand the da'wah material in inspiring devotion, researchers used content analysis, documentation and interviews. The results of research conducted on the inspirational Instagram account that uses a video about the contents of the da'wah content with the type of video poster. The use of the vidgram feature with the poster model becomes a da'wah media. Da'wah material conveyed by Ahmad Mustofa includes material Aqeedah, Shari'a and Morals. The implication of this research is that the instagram user interest in the video content of the vidgram feature becomes very important in conveying Islamic messages and da'wah. Abstrak Penelitian ini merupakan penelitian terhadap isi konten dakwah di media akun instagram asam inspiratif. tujuan dari penelitian ini adalah bagaimana isi konten dakwah di media akun instagram inspiratif dan bagaimana cara penyampaian dakwah di video inspirasi asmam. Metode penelitian yang digunakan adalah kualitatif sedangkan pendekatan yang digunakan untuk memahami dakwah wah materi dalam menginspirasi pengabdian, peneliti menggunakan analisis isi, dokumentasi dan wawancara. Hasil penelitian yang dilakukan pada akun instagram inspiratif yang menggunakan video tentang isi konten dakwah dengan jenis video poster. Penggunaan fitur vidgram dengan model poster menjadi media dakwah. Materi dakwah yang disampaikan Ahmad Mustofa meliputi materi Aqidah, Syariat dan Akhlak. Implikasi dari penelitian ini adalah minat pengguna instagram terhadap konten video fitur vidgram menjadi sangat penting dalam menyampaikan pesan dan dakwah Islami.